Reproductive biology of the limpet (patelloida saccharina) from Taklong Island, Southern Guimaras. - Ontoy, Angel Florie Leigh
The reproductive biology of Patelloida saccharina was studied on a rocky in Taklong Island, Southern Guimaras. Limpets of varying sizes were randomly collected in September 2016 snd December 2016, corresponding to the monsoon seasons (Southwest and Northeast) in the Philippines. Collected samples ranged from 20.7 - 32.8 mm in shell length (SL) for females, whereas male sizes ranged from 21.9 - 34 mm SL. Size (SL) at sexual maturity was 22.2 mm and 20.7 mm, for males and females, respectively. For both sampling periods, sex ratio between males and females showed no significant differences (p > 0.05). Mean gonadosomatic index (GSI in %) values for females (12%) were higher than males (9%). Investment in gonads during the Southwest monsoon (15%) was also higher than in Northeast monsoon (5%) indicating that limpets invest more of the energy reserves in reproduction during the Southwest. Limpet gonads were also examined using histological analysis to assess gonad maturation and, at the same time, ascertain GSI analysis. There was no observed immature stage of gonad development for both sexes in both seasons. This may be due to the limited range in the sizes of the samples collected where most individuals measure > 20 mm shell length. In the Southwest monsoon, 40% of males were mature whereas females constituted 33% of the mature stage. For the late developing stage, 17% were males while 10% were females. In Northeast monsoon, males were mostly in the late developing stage. For both sexes, the occurrence of mature limpets was high in the Southwest whereas no mature individuals were encountered in the Northeast. The reproductive biology of the limpet P. saccharina could be better studied if a wide range of sizes were collected and examined. Furthermore, increasing the duration of the sampling (e.g. 1 year) could yield to a better picture of the reproductive activity of this limpet.